Measuring interactions between polydimethylsiloxane and serum proteins at the air-water interface - Liao, Zhengzheng (Langmuir : the ACS journal of surfaces and colloids, 2013)
The interaction between synthetic polymers and proteins at interfaces is relevant to basic science as well as a wide range of applications in biotechnology and medicine. One particularly common and important interface is the air-water interface (AWI). Due to the special energetics and dynamics of molecules at the AWI, the interplay between synthetic polymer and protein can be very different from that in bulk solution. In this paper, we applied the Langmuir-Blodgett technique and fluorescence microscopy to investigate how the compression state of polydimethylsiloxane (PDMS) film at the AWI affects the subsequent adsorption of serum protein [e.g., human serum albumin (HSA) or immunoglobulin G (IgG)] and the interaction between PDMS and protein. Of particular note is our observation of circular PDMS domains with micrometer diameters that form at the AWI in the highly compressed state of the surface film: proteins were shown to adsorb preferentially to the surface of these circular PDMS domains, accompanied by a greater than 4-fold increase in protein found in the interfacial film. The PDMS-only film and the PDMS-IgG composite film were transferred to cover glass, and platinum-carbon replicas of the transferred films were further characterized by scanning electron microscopy and atomic force microscopy. We conclude that the structure of the PDMS film greatly affects the amount and distribution of protein at the interface